Programa educativo de estrategias con enfoque intercultural para mejorar la identidad cultural en los estudiantes de la institución educativa N° 6010210 de nivel primaria río amazonas, distrito de Punchana 2024 - Galindo Arimuya, Euler (2025)
This research pursued the purpose of determining whether the application of the strategies program with an intercultural approach improves the regional identity of the I.E. students. 6010210 at the primary level, in the district of Punchana, in 2024. An evaluative research was structured, with a quasi-experimental pretest-posttest design, which was made up of an experimental group (21 schoolchildren) and a control group (21 schoolchildren) who were selected from a population of 52 students from first to sixth grade. The results inferred from the analysis of statistical data showed an improvement in the cultural identity of the students in the experimental group after the application of the program in relation to the control group. The Mann-Whitney U test reported a p-value less than 0.001; Therefore, the significant differences in the post-test were confirmed and the program proved to be effective in strengthening regional identity. The conclusions indicated that these results support the general hypothesis, since pedagogical strategies with an intercultural approach adapted to the reality of the area contribute to the comprehensive development of students and the conservation of cultural identity in intercultural educational circumstances.